Effect of washing time and storage of raw Material on Surimi and Kamaboko of Tilapia (Oreochromis sp.) - Eka Saputra (Universitas Airlangga, 2018)
This study aim was to determine the effect of washing and raw materials on frozen storage on the quality of surimi and kamaboko from raw material of tilapia (Oreochromis sp). There were three types of raw materials used, namely minced fish, surimi, and surimi with addition of sorbitol, with three washing treatments and four weeks frozen storage period observed every week. The method used consisted of measurements of pH, water content, bite test, and folding test. Then the results obtained for the best kamaboko tilapia (Oreochromis sp) were obtained from fillet raw materials compared to the raw material of Minced fish and raw materials of Minced Fish + Sorbitol, with a frequency of washing once and frozen storage for 3 weeks.